Total Syntheses of Antimalarial Cyclic Tetrapeptides: Koshidacins A and B via Olefin Cross-Metathesis Reactions - Yang, Kun; Tong, Yue; Li, Tianhao; Sun, Yuanjun; Wang, Liang; Chen, Yue (Synthesis, 2025)
In this study, we present the first total syntheses of koshidacins A and B, antiplasmodial cyclic tetrapeptides from fungus, by assembling the side chain in late stage through olefin cross-metathesis. Additionally, the two diastereoisomers 8,9-epi-koshidacin A and 9-epi-koshidacin B were also synthesized by our synthetic route.
Keywords: koshidacin A; koshidacin B; total synthesis; cross-metathesis; antiplasmodial; cyclic tetrapeptides